A Systematic Literature Review of Local Food, Local Product, and Community Engagement in Rural Tourism - Adhikari, Sandeep (Janaprakash Journal of Multidisciplinary Research, 2024)
This systematic literature review aims to assess the current state of knowledge in rural homestays in terms of the use of local product, especially local food and community engagement in tourism academic literature. With reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart, the researcher reviewed 25 studies published in the selected journals from 2008 to 2023. The review explores how sustainable rural homestays have been previously researched in terms of local food, local product, and community engagement. The review sheds light on sustainability and rural homestay tourism from the perspective of use of typical products along with contents addressed by authors suggesting future research directions. All the reviewed papers have highlighted the significance of local food in the homestays considering its association with the tourist satisfaction, destination memory, and sustainable tourism practices. The entrepreneurial aspects of rural tourism, the utilization of modern tools and technology to enhance tourism practices and attract tourists, and the incorporation of locally available crops into the menus of local homestay projects are key areas that have been overlooked in the studies reviewed.